2017
DOI: 10.18203/2319-2003.ijbcp20173735
|View full text |Cite
|
Sign up to set email alerts
|

A study of hypoglycemic effect of Caesalpinia bonduc extract on alloxan induced diabetic albino rats

Abstract: Background: The objective of the study was to scientifically investigate the oral hypoglycemic activity of Caesalpinia bonduc on Alloxan induced diabetic albino rats. To compare the hypoglycemic effect of Caesalpinia bonduc with that of the standard drug Glibenclamide used in the treatment of diabetes mellitus.Methods: Adult healthy albino rats of wister strain of either sex weighing 150-200gms were included in the study. The animals were divided into 4 groups namely control, diabetic control, standard and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Oral administration of ESECB extract considerably reduced the levels of insulin and testosterone indicating the suppressive effect of insulin resistance. Previous studies by Nadaf et al (2017) and Ghosh et al (2012) have showed the hydro alcoholic extract has the potential of reducing blood glucose level. According to Shukla et al (2011), the phytoconstituents present in the C. bonducella considerably reduces the insulin resistance.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Oral administration of ESECB extract considerably reduced the levels of insulin and testosterone indicating the suppressive effect of insulin resistance. Previous studies by Nadaf et al (2017) and Ghosh et al (2012) have showed the hydro alcoholic extract has the potential of reducing blood glucose level. According to Shukla et al (2011), the phytoconstituents present in the C. bonducella considerably reduces the insulin resistance.…”
Section: Discussionmentioning
confidence: 90%
“…Administration of antiprogesterone Mifepristone RU486 (4 mg /0.2 ml oil) to 4 days estrous cyclic rats over eight consecutive days starting on the day of estrus (day 1) as per Sanchez-Criado et al (1993) method. To observe and monitor the development of PCOS condition in the rats, by irregular estrous cycle daily, vaginal smear test was conducted followed by the Mifepristone RU486 injection.…”
Section: Induction Of Pcos By Mifepristone In Female Ratsmentioning
confidence: 99%
See 1 more Smart Citation